USE OF INFORMATION TECHNOLOGIES IN SUPERVISION REMOTE PRACTICE: DATA SECURITY - Dubinins, Kirils; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Provision of remote services became relevant all over the world, during the 2020 COVID-19 pandemic. Latvian supervisors were also forced to transfer their practice to the digital space as well. COVID-19 pandemic challenges opened a wider range of opportunities for improvement remote practice. Pandemic also highlighted the risks associated with lack of relevant competences. At the global level over the last decade, risks associated with remote counselling summarized in guidelines, providing professionals with examples of best practice. In Latvia, on other hand, such guidelines have not adopted yet.This study developed with the aim to find out the awareness of Latvian supervisors about the risks (cyber security) of using information technology and the protection of personal data in the conditions created by the COVID-19 pandemic.To find out how Latvian supervisors are aware about the risks of using information technology (cyber security) and personal data protection, a survey conducted among Latvian supervisors and organizing an expert panel discussion, scientific strength of the study ensured by data triangulation.The obtained results allowed to conclude that the COVID-19 pandemic highlighted the need for supervision remote practice, at the same time the research data show that the awareness of Latvian supervisors about the risks of information technology use (cyber security) and personal data protection is medium to low.The results of the research show that in the education of Latvian supervisors it is necessary to allocate place for the acquisition of information technology (cyber security) risk and personal data protection regulation.This research emphasizes the importance of several supervisors’ competences such as digital knowledge and personal data protection, however further research is needed to find the most effective methods how to improve these competences.